Custom-shaped metal nanostructures based on DNA origami silhouettes - Shen, Boxuan; Linko, Veikko; Tapio, Kosti; Kostiainen, Mauri A; Toppari, J Jussi (Nanoscale, 2015)
The DNA origami technique provides an intriguing possibility to develop customized nanostructures for various bionanotechnological purposes. One target is to create tailored bottom-up-based plasmonic devices and metamaterials based on DNA metallization or controlled attachment of nanoparticles to the DNA designs. In this article, we demonstrate an alternative approach: DNA origami nanoshapes can be utilized in creating accurate, uniform and entirely metallic (e.g. gold, silver and copper) nanostructures on silicon substrates. The technique is based on developing silhouettes of the origamis in the grown silicon dioxide layer, and subsequently using this layer as a mask for further patterning. The proposed method has a high spatial resolution, and the fabrication yields can approach 90%. The approach allows a cost-effective, parallel, large-scale patterning on a chip with fully tailored metallic nanostructures; the DNA origami shape and the applied metal can be specifically chosen for each conceivable implementation.